Enhancement of Space-Time Receiver Structure with Multiuser Detection for Wideband CDMA Communication Systems - Subramaniam, Jeevan Rao (2006)
Wideband CDMA (WCDMA) which has been accepted as one of the radio access technology for third generation (3G) systems has many advantages such as efficient spectrum utilization and variable user data rates. However, multiple access interference (MAI) is a major constraint limiting the capacity of the system. Multiuser detection and smart antenna technologies are capable of increasing the system capacity through mitigation of such impairment. In this thesis, a combination of spatial signal processing with temporal signal processing is proposed. Additionally, the space-time receiver structure is combined with multiuser detection to further enhance the system. We propose and analyze different combined space-time linear multiuser detection configurations in an uplink mobile radio communications channel that incorporates the spatial temporal parameters. The performance of these receivers is evaluated as a function of the number of antenna elements, Rake fingers and number of users. We consider two different pilot symbol assisted adaptive beamforming algorithms, Least Mean Square (LMS) and Recursive Least Square (RLS). The algorithms are used to adjust the weights of the antenna array to form the appropriate beam patterns to track the desired user and null interfering users. The adaptive algorithms are evaluated as a function of the number of iterations it takes to converge and its transmission performance are compared. Additionally, two different linear multiuser detection techniques, Decorrelator and linear Minimum Mean Square Error (MMSE) strategies are used in conjunction with the combined receiver structure.The proposed combined Space Time Multiuser Detector which is suitable for WCDMA systems is shown to provide significant gain in transmission performance and system capacity. It is shown via simulation that the combined RLS adaptive algorithm with the linear MMSE multiuser detector provides the best overall performance. The simulation result also shows that the combined receiver structure is robust in the presence of strong interference due to high data rate users.